EFFECT OF CONCENTRATION OF EXTRACT ONION (Allium Cepa L.) ON GROWTH CUTTINGS SHOOTS SOME ACID ORANGE (Citrus Sp.) - Irna Syofia; Rahmi Zulhida; Muhammad Irfan (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2017)
This study used a randomized block design Factorial with two factors, namely the differences of some type sour orange (Citrus sp) (J) with 3 levels ie J1 citrus musk (Citrus mitis), J2 lime, J3 (Citrus hystrix). The second factor is the provision of onion extract concentration (B) with 3 traf, namely (B1) onion extract concentration of 25%, (B2) onion extract concentration of 50%, (B3) concentration of garlic extract merah75%. The results showed growth of shoot cuttings of lemon give the best effect against high Parameter shoots, number of leaves, number of shoot and root length. Onion extract with a concentration of 75% effect on age parameters appear shoots, shoot height, leaf number, number of shoot and root length. There is no interaction between several types of sour orange and red onion extract concentration levels on all parameters of observation.Keyword: Concentration, Extrack Onion , Acid Orange